Pretty in Prozac: The role of social connectedness in the declining life satisfaction of Australian females - Ulichny, Jen; Ambrey, C; Fleming, C (My University, 2014)
This paper investigates if social connectedness presents a possible explanation for the observed declines in self-reported female life satisfaction in Australia over the first decade of the 21st Century. Results indicate a positive association between all four measures of social connectedness and life satisfaction. Trends in social connectedness however, are less clear; participation in a hobby or community-based club or association has declined, as has frequency of social interaction. In contrast, sense of belonging and tangible support have both increased. There is some indication that the quality and quantity of social interactions differs between males and females and may play a role in declining life satisfaction. Therefore, fostering social connectedness would appear to be one channel through which social welfare might be promoted.
Keywords: Health -- Wellbeing; Social Capital; Gender -- Female; Satisfaction -- Life; Gender; Health and wellbeing; Health; Satisfaction; Social Capital; Gender; Wellbeing; Life; Female; Gender; Health and wellbeing